Message - Alexander, Idoko (Universal Journal of Pharmaceutical Research, 2019)
With an immense sense of approbation and unalloyed concession, I appreciate my appointment as an editorial board member of Universal Journal of Pharmaceutical Research (UJPR). My sincere and heart-felt congratulation to all members of the editorial board for these milestone achievements of three successful volumes and issues of the UJPR. Obviously, all these would not be possible without the unswerving high put-through efforts of members of the board who took a painstaking and guided constructive criticisms process in the review of accepted manuscripts, maintaining and updating UJPR’s standard. Such excellent and thorough manuscript review process is encouraged to produce a UJPR of high quality and repute among other international/world journals. The progress made thus far by our journal is un-doubtly a collective and collaborative effort by both authors and editorial board members. The provided platform for meaningful suggestions targeted at promoting our journal has immensely helped and more cutting edge suggestions and contributions are welcome until we have Universal Journal of Pharmaceutical Research a SCOPUS, THOMSON REUTERS, ISI and SCIMAGO indexed journal. As a follow up, in this era were research has taken a multidisciplinary approaches, involving diversified interconnected methods touching different fields, UJPR encourages board members and authors alongside their colleagues and students to submit original articles having citations of relevant literature published in UJPR in their subsequent publications.